Benchmark of Simplified Time‐Dependent Density Functional Theory for UV–Vis Spectral Properties of Porphyrinoids. Issue 1 (24th November 2019) - Batra, Kamal; Zahn, Stefan; Heine, Thomas
Abstract: Time‐dependent density functional theory is thoroughly benchmarked for the predictive calculation of UV–vis spectra of porphyrin derivatives. With the aim to provide an approach that is computationally feasible for large‐scale applications such as biological systems or molecular framework materials, albeit performing with high accuracy for the Q‐bands, the results given by various computational protocols, including basis sets, density‐functionals (including gradient corrected local functionals, hybrids, double hybrids and range‐separated functionals), and various variants of time‐dependent density functional theory, including the simplified Tamm–Dancoff approximation, are compared. An excellent choice for these calculations is the range‐separated functional CAM‐B3LYP in combination with the simplified Tamm–Dancoff approximation and a basis set of double‐ζ quality def2‐SVP (mean absolute error [MAE] of ≈0.05 eV). This is not surpassed by more expensive approaches, not even by double hybrid functionals, and solely systematic excitation energy scaling slightly improves the results (MAE ≈0.04 eV). Abstract : Time‐dependent density functional theory (TD‐DFT) is benchmarked for predicting UV–vis spectra of porphyrin derivatives. Among local, hybrid, range‐separated hybrid and double hybrid density functionals, CAM‐B3LYP is found to show superior performance compared to all others. Interestingly, the semi‐empirical simplified Tamm–Dancoff approximation outperforms all other variants of TD‐DFT for this compound class, and large basis sets do not improve the results.